Natural infection of a variant pseudorabies virus leads to bovine death in China. Issue 2 (6th December 2019) - Cheng, Zilong; Kong, Zhengjie; Liu, Peng; Fu, Zhendong; Zhang, Jiandong; Liu, Mengda; Shang, Yingli
Abstract: Pseudorabies virus (PRV) infects numerous species of domestic and wild animals leading to severe diseases especially in swine and cattle. Since 2011, the variant PRVs were identified in pigs, which were genetically different from classic strains. Although variant PRV infection is widely observed in pigs, there is still no report of variant PRV infection in cattle. Here, we reported a natural infection of variant PRV leading to acute bovine death in Eastern China. Our study suggests that the new variant PRV strains could be a potential threat to cattle industry and possibly to the public health of human.